Effects of feeding-phase duration and anticoccidial inclusion on growth and carcass traits of broilers - Restrepo Rojas, Oliver; Múnera Bedoya, Oscar D; Giraldo Mejía, Angel M; Quiñones Segura, Libardo (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: A typical broiler production program includes three feeding phases: Pre-starter (from day 1 to 10), Starter (11-21 days), and Grower (from day 22 to slaughter). The program should allow the bird to express its genetic potential and respond to the nutritional challenges. Objective: To determine the effect of duration of the starter and grower phases on growth performance parameters (feed intake and feed conversion), mortality, skin pigmentation, and carcass yield in broiler chickens. Methods: A total of 1,500 Ross 308 AP male broilers were randomly assigned to five feeding programs with different duration, feed presentation (pellet vs. crumble), and anticoccidial (narasin + nicarbazin vs. salynomicin). The variables evaluated were growth performance (body weight, feed intake, and feed conversion), carcass (weight and yield), breast weight and yield, and skin pigmentation. Statistical evaluations were conducted on d 28 and 40 of age. Results: On d 28 of age, differences (p<0.05) were observed for body weight and feed conversion, but not for feed intake. T4 and T5 resulted in the best weight and feed conversion. Differences (p<0.05) were recorded on d 40 for body weight, with higher values in T4 and T5 compared to T1. Carcass weight differed between T1 and T4 (p<0.05), without difference for carcass or breast performance. The statistical analyses of carcass pigmentation showed an effect on redness (“a”) and yellowness (“b”) at d 28. Conclusions: Body weight and feed conversion of broilers from d 22 to 28 improve by extending the starter phase one week, using pelleted feed added with an ionophore anticoccidial. Skin pigmentation of broilers at slaughter is not affected by restricting pigment intake for one week.